Burkina Faso - Promoting Growth, Competitiveness and Diversification : Country Economic Memorandum, Volume 2. Sources of Growth - Key Sectors for Tomorrow - World Bank (Washington, DC, 2013)
The main conclusion of Country Economic Memorandum is that the previous model of extensive growth has now exhausted its potential and must be renewed. Given the existing population dynamics, low environmental tolerance due to its Sahelian climate and competition forces imposed due to its open economy, Burkina Faso is heavily investing in growth based on increased productivity to overcome its low level of initial human capital, capacity constraints and regulation. To help define the new model of development of Burkina Faso, the Country Economic Memorandum is exploring growth based on productivity both at macro-, meso-economic or sectoral, micro and institutional levels only. It also assesses the sustainability of growth in the human, demographic, financial, fiscal and physical infrastructure. Wherever possible, it evaluates the performance of previous development programs and provides diagnostics on problems. It analyzes the current situation in terms of challenges and opportunities. Several major constraints on growth have been identified and the Memorandum offers practical ways to reduce or mitigate them. These constraints are: i. The frequency of exogenous shocks on agriculture in Burkina Faso, especially cotton, significantly slows the socio-economic development; ii. The real appreciation of the exchange rate has eroded the price competitiveness; iii. The country's attractiveness to foreign direct investment, despite significant progress in the business environment, limited growth potential; iv. The high fertility rates impede growth per capita and social development beginning with human capital; v. Environmental constraints limit the extensive growth of agriculture, while food security is always a challenge for human development; vi. The vulnerability of poor households prevents them from truly engaging in productive economic activities; vii. Constraints on institutional and human capacities reduce the effectiveness of public policies. The first volume of the Memorandum emphasizes the need for Burkina Faso to consider the macroeconomic and microeconomic constraints to growth and competitiveness, draws attention to the low sophistication of its exports and suggests policy instruments to facilitate the promotion of export and investment led by the private sector. The second volume emphasizes (i) the need for appropriate choices to ensure the viability of the cotton sector, (ii) the development of supply chains to achieve food security, growth and import substitution, (iii) the important role in the mining sector for growth, with good revenue management, and finally (iv) the potential of tourism as an industry will depend on the service quality improvements and the accommodation capacity and infrastructure. The third volume identifies the actions necessary to (i) address the issues of demographic change through better information, education and communication campaigns to bring about behavioral changes, (ii) develop instruments of risk management to manage the risks of economic, social, health, natural and food security, (iii) improve the country's access to regional and international markets, better connections to regional transport infrastructure, electricity, and telecommunications, water services and improved irrigation systems, (iv) exploiting the financial intermediation by new mechanisms of access to credit, reform the financial sector and institutional capacity building in financial management and risk in the business sector, and (v) create and use the budget by prioritizing expenditures, ensuring the collection of revenue and increasing the flow of aid.